Photocatalytic H2O-to-H2O2 synchronized oxidation of an organic pollutant by carbon dot/g-C3N4 composites - Hsu, Je-Wei; Wei, Ling-Wei; Chen, Chiaying; Wang, H. Paul (Journal of cleaner production, 2022)
Photocatalytic oxidation of organic pollutants using the solar energy is environmentally and economically attractive for developing an energy sustainable organic wastewater treatment process. Here, we employed the impregnation-thermal method to prepare novel carbon dot (CD) dispersed graphitic carbon nitride (g-C3N4) (GCN)/pyromellitic dianhydride (PDI) (CD/GCN/PDI) composites for photocatalytic H2O-to-H2O2 and on-site oxidation of organic pollutants in contaminated or waste water. After a 5-h visible-light irradiation, 252 μM of H2O2 can be yielded by the CD/GCN/PDI composites. The CD, serving as an electron reservoir, dispersed on the GCN/PDI composite (i.e., CD0.003/GCN/PDI) facilitates the separation of photo-excited electrons to promote the two-electron reduction O2-to-H2O2 (O2→˙O2−→H2O2). Most importantly, it also on-site activates H2O2 to form ·OH radicals (H2O2→·OH) to enhance oxidation of organic pollutants (e.g., methylene blue and bisphenol A). The ·OH, ∙O2−, and photogenerated h+ account for 4–5%, 14–18%, and 20–25% oxidation of organic pollutants under visible-light irradiation for 3 h, respectively. The CD0.003/GCN/PDI composite was also tested for photocatalytic oxidation of the organic pollutant under visible-light irradiation for at least 12 h to demonstrate its photostability and reusability. This visible-light photocatalytic H2O-to-H2O2 for the enhanced oxidation of organic pollutants by the low-cost and metal-free CD/GCN/PDI composites using solar energy was developed to demonstrate the feasibility of an energy self-sufficient organic wastewater treatment process. Photocatalytic H2O-to-H2O2 synchronized oxidation of an organic pollutant (R) by the CD/GCN/PDI composites. The CD, serving as an electron reservoir, dispersed on the GCN/PDI composite (i.e., CD0.003/GCN/PDI) facilitates the separation of photo-excited electrons to increase the two-electron reduction O2-to-H2O2 (O2→˙O2−→H2O2). Most importantly, it also on-site activates H2O2 to form ·OH radicals (H2O2→·OH) to enhance oxidation of organic pollutants (e.g., methylene blue and bisphenol A). Other on-site activated highly reactive species such as ∙O2− and photogenerated h+ also contribute to oxidation of organic pollutants in wastewater. [Display omitted] •The novel CD/GCN/PDI can retard charge recombination for a high yield of H2O2.•The CD/GCN/PDI can induce highly reactive species to enhance organic pollutant oxidation.•The solar-driven H2O-to-H2O2 by CD/GCN/PDI shows energy self-sufficient water clean-up.